Rick Steves Italy for food lovers 2023 - Steves, Rick, 1955-; Plotkin, Fred (Avalon Travel, 2023)
Experience the best of Italy through the timeless pleasures of its cuisine. With this fun and practical handbook to eating well in Italy, you'll learn how to appreciate good food the way Italians do. Includes food and wine specialties in each of Italy's 20 regions, practical tips on enjoying dining on any budget and navigating the menus, and a food glossary to help cross any language barriers. Plus, a list of 100 restaurants handpicked by co-authors Rick Steves and Fred Plotkin. --